Selective doping of Ni2+ in highly transparent glass-ceramics containing nano-spinels ZnGa2O4 and Zn1+x Ga2−2x Ge x O4 for broadband near-infrared fiber amplifiers - Zhigang Gao (Nature Portfolio, 2017)
Abstract Selective doping of Ni2+ in octahedral sites provided by nanocrystals embedded in glass-ceramics (GCs) is crucial to the enhancement of broadband near-infrared (NIR) emission. In this work, a NIR emission with a full-width-at-half-maximum (FWHM) of 288 nm is first reported from ZnGa2O4: Ni2+ nano-spinels embedded GCs with excellent transparency. A comparison is made of the NIR luminescence properties of Ni2+ doped GCs containing ZnGa2O4, germanium-substituted ZnGa2O4 nano-spinels (Zn1+x Ga2−2x Ge x O4), and Zn2GeO4/Li2Ge4O9 composite nanocrystals that are free of Ga3+. The results show that ZnGa2O4: Ni2+ GCs exhibit a significantly enhanced NIR emission. The incorporation of the nucleating agent TiO2 is favored in terms of the increased luminescence intensity and prolonged lifetime. The possible causes for the enhancement effect are identified from the crystal structure/defects viewpoint. The newly developed GCs incorporate good reproducibility to allow for a tolerance of thermal treatment temperature and hence hold great potential of fiberization via the recently proposed “melt-in-tube” method. They can be considered as promising candidates for broadband fiber amplifiers.